Composition and Yield of Colostrum and Milk from Murrah and “Murrah x Carabao” Crosses in the Philippines - O. L. Bondoc; T. Almendral-Saludes; A. G. Tandang; A. R. Bustos; A. R. Ramos; A. O. Ebron (Faculty of Animal Science, Bogor Agricultural University, 2021)
This study compared the composition, yield, and freezing point of buffalo colostrum and milk collected on the 30th, 60th, and 90th day of lactation from purebred Murrah and its crosses with the Philippine Carabao. A total of 133 milk samples were collected from 36 buffaloes (20 purebred Murrah and 16 “Murrah x Carabao” crosses) and evaluated for fat, protein, and lactose content, solids non-fat (SNF), total solids, and freezing point. Colostrum contained significantly (p<0.05) more protein, SNF, total solids, and higher freezing point, but less moisture and lactose, and were produced in lower amounts than milk obtained on different days of lactation. Fat percentage was not significantly different (p>0.05) between colostrum and milk. Colostrum from Murrah buffaloes had more protein but less fat and colostrum yield than “Murrah x Carabao” crosses. Among crossbred buffaloes, the F2 “75% Murrah – 25% Carabao” crosses produced more colostrum than F1 “50% Murrah – 50% Carabao” (p<0.05). Older buffaloes also produced more colostrum. Milk parameters were similar for Murrah and “Murrah x Carabao” crosses, except for test-day milk yield, which was significantly higher in “Murrah x Carabao” crosses. The F1 crossbred buffaloes had milk containing more lactose and SNF, but lower freezing point than milk from F2 crossbred buffaloes. Buffaloes, already with more lactations, had higher test-day milk yield but with lower fat and total solids. High monthly temperature reduced test-day milk yield. In conclusion, breed differences, age at calving, number of lactations, and high monthly temperature may have caused changes in the composition and yield of buffalo colostrum and milk.